(untitled) (Orfeu, 2022)
This article is a reflection proposal on the perception of the transformations operated in the cartographies of knowledge in crisis time, from the I virtual trombone seminar, promoted by the Coletivo Brasileiro de Trombonistas (CBT) during the Covid-19. As a theoretical background, we use the concept of intellectual pandemic and propose conceptual tools for realising some necessary shifts toward an Ecology of Knowledges. The aim is to understand how, in isolation contexts, the processes of knowledge constitution are developed, considering the particular case of the CBT. The research questioned how the logic of the ongoing intellectual pandemic is articulated with the constitution of knowledge in virtual transits. The reflection and study of the participants’ narratives enabled the definition of 8 main categories of analysis and the construction of social cartography, which led us to answer the central questions raised in this study.